Development of gas turbine combustor preliminary design methodologies and preliminary assessments of advanced low emission combustor concepts - Khandelwal, Bhupendra (Cranfield University, 2012)
It is widely accepted that climate change is a very serious environmental concern. Levels of carbon dioxide (CO2) and other emissions in the global atmosphere have increased substantially since the industrial revolution and now increasing faster than ever before. There is a thought that this has already led to dangerous warming in the Earth’s atmosphere and relevant changes around. Emissions legislations are going to be stringent as the years will pass. Hydro carbon fuel cost is also increasing substantially; more over this is non- renewable source of energy. There is an urgent need for novel combustor technologies for reducing emission as well as exploring alternative renewable fuels without effecting combustor performance. Development of novel combustors needs comprehensive understanding of conventional combustors. The design and development of gas turbine combustors is a crucial but uncertain part of an engine development process. At present, the design process relies upon a wealth of experimental data and correlations. Some major engine manufacturers have addressed the above problem by developing computer programs based on tests and empirical data to assist combustor designers, but such programs are proprietary. There is a need of developing design methodologies for combustors which would lead to substantial contribution to knowledge in field of combustors. Developed design methodologies would be useful for researchers for preliminary design assessments of a gas turbine combustor. In this study, step by step design methodologies of dual annular radial and axial combustor, triple annular combustor and reverse flow combustor have been developed. Design methodologies developed could be used to carry out preliminary design along with performance analysis for conventional combustion chambers. In this study the author has also proposed and undertaken preliminary studies of some novel combustor concepts. A novel concept of a dilution zone less combustor has been proposed in this study. According to this concept dilution air would be introduced through nozzle guide vanes to provide an optimum temperature traverse for turbine blades. Preliminary study on novel dilution zone less combustor predicts that the length of this combustor would be shorter compared to conventional case, resulting in reduced weight, fuel burn and vibrations. Reduced fuel burn eventually leads to lower emissions. Another novel concept of combustor with hydrogen synthesis from kerosene reformation has been proposed and a preliminary studies has been undertaken in this work. Addition of hydrogen as an additive in gas turbine combustor shows large benefits to the performance of gas turbine engines in addition to reduction in NOx levels. The novel combustor would have two stages, combustion of ~5% of the hydrocarbon fuel would occur in the first stage at higher equivalence ratios in the presence of a catalyst, which would eventually lead to the formation of hydrogen rich flue gases. In the subsequent stage the hydrogen rich flue gases from the first stage would act as an additive to combustion of the hydrocarbon fuel. It has been preliminary estimated that the mixture of the hydrocarbon fuel and air could subsequently be burned at much lower equivalence ratios than conventional cases, giving better temperature profiles, flame stability limits and lower NOx emissions. The effect of different geometrical parameters on the performance of vortex controlled hybrid diffuser has also been studied. It has been predicted that vortex chamber in vortex controlled hybrid diffuser does not play any role in altering the performance of diffuser. The overall contribution to knowledge of this study is development of combustor preliminary design methodologies with different variants. The other contribution to knowledge is related to novel combustors with a capability to produce low emissions. Study on novel combustor and diffuser has yielded application of two patent applications with several other publications which has resulted in a contribution to knowledge. A list of research articles, two patents, awards and achievements are presented in Appendix C.
Keywords: Combustor; Gas Turbine Combustor Design; Novel Combustors; Hydrogen synthesis; kerosene reforming; Hydrogen enriched combustion